2013
DOI: 10.1007/s00383-013-3322-8
|View full text |Cite
|
Sign up to set email alerts
|

Cloacal malformation variants in male

Abstract: None of the male cloacal patients presented in the neonatal period, proximal hypospadias was the common external genital abnormality and half of them had a vagina. Surgical outcome was satisfactory. The scarcity of reported cases of this group is a subject of further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 14 publications
0
23
0
Order By: Relevance
“…Bano et al reported four male patients with cloacal variants [9]. The next commonly related anomaly would be associated hypospadias and anorectal malformation.…”
Section: Discussionmentioning
confidence: 94%
“…Bano et al reported four male patients with cloacal variants [9]. The next commonly related anomaly would be associated hypospadias and anorectal malformation.…”
Section: Discussionmentioning
confidence: 94%
“…Although rare, such cases might be encountered as frequently as once or twice a year in a tertiary referral center (6). Cloacal anomaly is almost exclusively reported in female fetuses but may also occur in male fetuses (8).…”
Section: Discussionmentioning
confidence: 99%
“…(7/195) of Bangladeshi ARM patients had male cloacal malformations, which was significantly higher than previously reported percentage of 0.2%. 13 We assume that this was due to increased referral to the participating institute in Bangladesh since the publication of male cloacal malformation in 2013. 13…”
Section: Relative Incidence Of Arm Subtypesmentioning
confidence: 99%
“…13 We assume that this was due to increased referral to the participating institute in Bangladesh since the publication of male cloacal malformation in 2013. 13…”
Section: Relative Incidence Of Arm Subtypesmentioning
confidence: 99%